El discurso pedagógico oficial en Argentina (2003-2013): Trabajo docente e igualdad - Vassiliades, Alejandro (2014)
This article discusses the results of research on teaching practice regulations in Argentina. Using the conceptual tools of political analysis of the discourse, I will analyse some of the main elements of the official discourse between 2003 and 2013. I will raise the hypothesis that they were articulated around the discursive equivalence of educational inclusion-equality, and that it gave way to two streams of related meanings. One of them associated equality and educational inclusion to the declaration of education as a social right, the centrality of the state, the return of the common good and the consideration of the diversity; the other associated equality and educational inclusion to the idea of centrality of teaching, to work with situations of “educational inequality” – such as the age-grade distortion and failure – and “social vulnerability”, and the promotion of alternative modes of organization.